Não aplicabilidade do princípio da insignificância aos portadores de maus antecedentes ou reincidentes em pequenos delitos - Pascolati Junior, Ulisses Augusto (2012)
This work proposes to analyze the applicability of insignificance s principle for whom has criminal record or that is recidivist in misdemeanor. The insignificance s principle is grounded on constitutional and legal principles and it is a restrictive interpretation vector of criminal type. Originated of roman aphorism minima non curat praetor , this principle, when recognized, renders the fact atypical if the conduct is absolutely insignificant, independently of subjective criterions. If relatively insignificant, the insignificance excludes culpability based on lack of need of punishment, considering a small injury to the individualized legal interest and a reduced disapproval agent. For those who have criminal record or that is recidivist in misdemeanor, the culpability must be maintained due to the disapproval of conduct is adequate. The acknowledgment considers necessity of a pacific social coexistence and attempting to avoid self-guardianship reactions, which on those situations imply necessity and obligation of punishment